ANALISIS STRATEGI PEMBIAYAAN PRIORITAS DANA DESA DI DESA MURUY KECAMATAN MENES KABUPATEN PANDEGLANG PROVINSI BANTEN - Siti Humaeroh; Suwaib Amiruddin; Rina Yulianti (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This study aims to establish a priority funding strategy for rural funds in Muruy Village, Menes District, Pandeglang Regency. After the enactment of Village Law No. 6 of 2014, the government allocated significant funds (APBDesa) for village management. The priority of rural funds for 2023 is regulated by Decree no. 8 of 2022 of the Minister of Rural Development, Privileged Region Development and Transmigration of the Republic of Indonesia. According to village authorities, the focus of rural funds in Muruy village for 2022-2023 is more on improving economy, human resources and health services, as well as improving education and management of natural disasters and unnatural events. This study used a qualitative descriptive design and data collection techniques through structured interviews. The results of the interviews then flowed into the SWOT analysis matrix (strengths, weaknesses, opportunities, threats). A priority funding strategy for rural funds can be established, prioritizing the development of infrastructure such as roads in different villages, and rural authorities' efforts to address weaknesses and threats can be achieved through even better coordination among village chiefs. and the community.